Discussion of Performance Measure Garbling Under Renegotiation in Multi-Period Agencies - Lambert, Richard A. (Journal of Accounting Research, 1999)
Richard A. Lambert, Discussion of Performance Measure Garbling Under Renegotiation in Multi-Period Agencies, Journal of Accounting Research, Vol. 37, Studies on Credible Financial Reporting (1999), pp. 215-221